Retrospective comparison between breast cancer tissue- and blood-based next-generation sequencing results in detection of PIK3CA, AKT1, and PTEN alterations - Moumita Chaki; Mona Benrashid; Subir Puri; Smruthy Sivakumar; Ethan S. Sokol; Josefa M. Briceno; Neil Vasan (Breast Cancer Research)
Abstract Background Based on the CAPItello-291 phase III trial results, capivasertib in combination with fulvestrant has been approved for patients with hormone receptor-positive/human epidermal growth factor receptor 2-negative advanced breast cancer harboring one or more PIK3CA, AKT1, and/or PTEN alterations. Given the growing interest in circulating tumor DNA (ctDNA) next-generation sequencing (NGS) to detect PIK3CA/AKT1/PTEN alterations, we retrospectively compared blood-based FoundationOne®Liquid CDx versus tumor tissue-based FoundationOne®CDx real-world data from patients with various breast cancer subtypes. Methods We utilized a database of patients profiled with FoundationOne®CDx and/or FoundationOne®Liquid CDx during routine clinical care. Analytical comparison of all pathogenic alterations in PIK3CA, AKT1, AKT2, AKT3, and PTEN, including alterations defined in the CAPItello-291 protocol (CAPItello-defined alterations), was performed in paired data from 289 patients with both tissue and liquid biopsies sampled within 90 days of each other. Results Overall positive percent agreement (PPA) for short variants across ctDNA tumor fraction (TF) subgroups in paired biopsy samples was: ctDNA TF ≥ 10%: PIK3CA, 93.9%; AKT1, 100%; PTEN, 100%; ctDNA TF 1%-10%: PIK3CA, 96.3%; AKT1, 100%; PTEN, 100%; ctDNA TF < 1%: PIK3CA, 34.7%; AKT1, 50.0%; PTEN, 37.5%. PPA for CAPItello-defined alterations was: ctDNA TF ≥ 10%: 92.5%; ctDNA TF 1%-10%: 97.1%; ctDNA TF < 1%: 33.9%. For PTEN homozygous deletions, PPA was 50.0% in cases with ctDNA TF ≥ 10%. Overall PPA for AKT2 and AKT3 copy number variations (CNVs) was 66.7% and 0%, respectively. Conclusions Blood-based NGS could offer a minimally invasive option to identify clinically relevant PIK3CA/AKT1/PTEN short variants in cases with ctDNA TF ≥ 1%. Confirmatory tissue-based NGS should be performed when blood-based NGS results are negative, especially when ctDNA TF is < 1% and for enhanced detection of CNVs in general.